Beyond the Classroom: The Emergence of Home Schooling as a Shift Away from Formal Schooling - Basnyat, Samjhana (Educational Journal, 2024)
The practice of teaching school-age children at home or in various locations other than schools is known as homeschooling. Home schooling is gaining momentum as a flexible and personalized alternative to formal education. It offers parents greater control over curriculum and learning pace, addressing individual student needs and educational gaps often unmet in traditional classroom settings. This article aims to present a concise overview of the key characteristics of homeschooling and to explore the underlying factors influencing parents’ decisions to decide on for home-based education for their children. This study employed a thematic literature review methodology, analyzing existing peer-reviewed empirical research on home schooling to identify key themes, benefits, and challenges. The review critically examines home schooling as a viable alternative to formal education in contemporary contexts. In this review, majority of studies on homeschooling find that it has an encouraging influence on learners compared to those who attend institutional schools; nevertheless, some studies arrange for contrary findings. In terms of social, cognitive, and emotional growth, maximum studies indicate that homeschooling produces distinctly better results than traditional schooling. The conclusions derived from these studies provide a summary of specifically selected research on the development of homeschooling, along with final reflections and recommendations for future research in this area home schooling is emerging as a flexible and personalized alternative to formal education, offering parents greater control over curriculum and learning pace. It challenges traditional schooling by addressing individual needs, especially in contexts where formal systems may be limited or ineffective.